Surveying the extent and wage consequences of education-job mismatches in the Philippine labor market - Melchor, Monica M. (2022)
The translation of educational investments into expanded employment opportunities and higher wages is among the ways in which a nation’s educational outcomes are deemed successful. However, while education-skill mismatches are prevalent in both developed and developing economies, there is a need to extensively analyze this gap in the developing economy context, owing to the lack of data and other constraints. This paper seeks to
estimate the extent of education-employment mismatches and the resulting wage consequences in the Philippine labor market. The results find that 39 percent of employed individuals are overeducated while over a quarter are
undereducated. Overeducated individuals earn only 5 percent more for a surplus
year of schooling, relative to required years of schooling, which have returns
of 7 percent to 19 percent. They underline the importance of labor market
policies for improved job-skills matching, for instance, through the reduction
of information asymmetries. Moreover, public subsidies must be reconsidered
for higher education that are premised on improved wage prospects or higher
productivity for highly educated individuals.
Keywords: Educational evaluation; Education job -- labor market